Paradigma Lokalisme Dalam Perencanaan Spasial - Sudaryono Sudaryono (Journal of Regional and City Planning, 2006)
This article attempts to offer the paradigm of localism as an umbrella for spatial planning. It emphasizes that today; in the practical world of planning works in Indonesia there is a strong need to take local values (to include social, cultural, and local politics) as basis for spatial planning. Six planning parameters are proposed to bring the paradigm into the real world, they are: (i) the radius of uniqueness (ii) spatial existence, (iii) spatial defense, (iv) local community strengthens (v) local solution, and (vi) moral obligation of planner.Keywords: localism, spatial planning, local uniqueness, local politics, spatial security, moral obligation